Feminisme Populer dalam Iklan Digital: Analisis Femvertising pada Konten Instagram @sascofficial Periode 2021-2025 - Adiputra, Novicky Alban (Besaung : Jurnal Seni Desain dan Budaya, 2025)
The discourse of feminism within commercial contexts often contains pseudo pro-women messages, particularly when feminist values are reduced to marketing strategies through femvertising. Within the beauty industry, brands utilize social media as a cultural space that enables the continuous reconstruction of female representations to be consumed visually and emotionally. Therefore, this study aims to uncover the visual and verbal meanings in the digital advertisements of Instagram @sascofficial by examining how feminist discourse is represented, the extent to which feminist values are commodified through femvertising, and the ideological messages conveyed. Using a qualitative approach, Roland Barthes’ semiotic analysis and Norman Fairclough’s critical discourse analysis were applied to five uploaded contents from 2021 to 2025. The findings show that @sascofficial reconstructs female figures into two types of representations, collective inclusive femininity and individual sensual femininity, which are both framed as forms of empowerment. The results also reveal that visual elements, emotions, and identity are combined to render popular feminism easily consumable within digital culture. Femvertising appears in varying intensities, both explicitly and implicitly, functioning to connect audiences with the brand and its products through a commodified form of feminist discourse. This study concludes that @sascofficial’s content from 2021–2025 does not contain an authentically pro-women message but instead operates within a structured femvertising framework designed to enhance sales by creating emotional bonds through deliberately constructed female figures.